Disaster Response Self-Efficacy of Students in the Nursing Department: A Cross-Sectional Study - Yılmaz, Dilek; Buran, Gonca (UI Scholars Hub, 2024)
Background: Nurses take on important roles in disasters. In this regard, the disaster response self-efficacy of nursing students must be evaluated. The study aimed to determine the self-efficacy of nursing students in disaster response. Methods: In this descriptive cross-sectional study, the study sample consisted of 207 nursing students who were in their third or fourth year attending the nursing department of a state university in the Marmara region of Türkiye between October and December 2023. Data were collected using a student description form and the disaster response self-efficacy scale. Results: The mean age of the study participants was 22.05 ± 2.23 years, 73.4% were female, 50.2% were in their third year of study, 90.3% felt a need for education on disaster nursing, and 76.8% stated that they did not have sufficient knowledge and skills relating to disasters. The students’ mean total score on the disaster response self-efficacy scale was 3.23 ± 0.68. In addition, the disaster response self-efficacy levels of students who stated they had sufficient knowledge and skills concerning disaster response were significantly higher than those of other students (p < 0.05). Conclusions: Students demonstrated a medium level of disaster response self-efficacy.